Kurswechsel in der deutschen Klimapolitik am Beispiel der energetischen Gebäudesanierung - Petrik Runst (Wirtschaftsdienst, 2016)
Um CO2-Emissionen zu vermeiden, schreibt der Gesetzgeber in Deutschland häufig direkte, ganz konkrete Eingriffe vor. Im Bereich der energetischen Gebäudesanierung wird im Detail festgelegt, wo und wie eingespart werden soll. Es liegt auf der Hand, dass mit so engen Vorgaben eine effi ziente Lösung häufig nicht erzielt werden kann. Der Autor plädiert für ein Umdenken in der deutschen Klimapolitik. – – Direct policy interventions with regard to building energy efficiency are necessarily abstract and therefore not always flexible enough to suit individual living conditions. They disregard local knowledge and cannot benefit from a decentralized search process which would ensue under a taxation scheme. Detailed central decision making is also vulnerable to lobbying by interest groups. The interview results presented here support the high costs and lacking fl exibility of current retrofi t guidelines. One theoretical as well as three actual retrofi t scenarios suggest that the costs of CO2-reduction under the current policy scheme lie between 300 and 1,000 Euro/ton. Indirect policy schemes are associated with abatement costs of 30 to 200 Euros per ton.
Keywords: Q4; Q48; P18; 330; Klimapolitik; Klimaschutz; Energiesparendes Bauen; Kritik; Deutschland